Ultrasound-Assisted Management for Tracheal Intubation in the Patient with Tracheal Diverticulum - Tingting Wan; Ya Gao; Changyi Wu (Case Reports in Anesthesiology)
Tracheal diverticulum (TD) is a rare disease. Due to the worldwide pandemic of COVID-19, the increase of routine preoperative chest CT examination has led to a higher detection rate of TD. Although TD is very rare, it is one of the reasons for difficult intubation and difficult ventilation. Improper treatment can cause severe airway emergencies such as diverticulum tearing, tracheal rupture, and subcutaneous or mediastinal emphysema. Unfortunately, there are few studies on TD, especially in perioperative airway and anesthesia management. This paper reports a case of TD found by preoperative chest CT examination who required tracheal intubation under general anesthesia. For the first time, ultrasound was used to confirm the position of tracheal tube and TD, and good results were achieved. This attempt provides a new idea and method for airway management in patients with TD.